2021
DOI: 10.1371/journal.pone.0258963
|View full text |Cite
|
Sign up to set email alerts
|

Differential systemic inflammatory responses after TAVI: The role of self versus balloon expandable devices

Abstract: Objective Transcatheter aortic valve implantation (TAVI) provokes early injury response, represented in part by dynamic changes in the inflammatory markers. The association of self-expanding valves (SEVs) and balloon-expandable valves (BEVs) with the consequent inflammatory response remains uncertain. Materials and methods Patients with severe symptomatic aortic stenosis who underwent transfemoral TAVI: SEVs or BEVs, from January 2010 to December 2019 were enrolled. Whole white blood cells (WBC) and subpopul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…The NLR has been identified as a predictive marker of systemic inflammation in various diseases. [15][16][17] NLR reflects the dynamic interaction between innate (neutrophils) and adaptive cellular immunological responses to disease and diverse pathological circumstances, The NLR has been associated with AKI. Yelgeç et al 18 found that post-procedural NLR was an independent risk factor for AKI (OR: 1.79; p=0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLR has been identified as a predictive marker of systemic inflammation in various diseases. [15][16][17] NLR reflects the dynamic interaction between innate (neutrophils) and adaptive cellular immunological responses to disease and diverse pathological circumstances, The NLR has been associated with AKI. Yelgeç et al 18 found that post-procedural NLR was an independent risk factor for AKI (OR: 1.79; p=0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The NLR has been identified as a predictive marker of systemic inflammation in a number of cardiovascular and non-cardiovascular diseases. [15][16][17] Following TAVI, the NLR has been linked to the development of AKI. [18][19][20] The average platelet volume (MPV) is a computerized measurement of platelet size.…”
Section: Introductionmentioning
confidence: 99%
“…A neutrophil-to-lymphocyte ratio can be used as a prognostic marker in TAVI patients [ 36 ]. TAVI-associated SIRS is more extensive with self-expanding compared to balloon-expandable devices [ 37 ]. This could be partially explained by more pronounced endothelial injury (due to oversizing and continuous pressure to surrounding tissues) and an increased inflammatory reaction to a foreign body placement (due to the presence of residual cells, DNA, and the alpha-Gal epitope in porcine-derived materials) of self-expanding devices [ 37 ].…”
Section: Framementioning
confidence: 99%
“…TAVI-associated SIRS is more extensive with self-expanding compared to balloon-expandable devices [ 37 ]. This could be partially explained by more pronounced endothelial injury (due to oversizing and continuous pressure to surrounding tissues) and an increased inflammatory reaction to a foreign body placement (due to the presence of residual cells, DNA, and the alpha-Gal epitope in porcine-derived materials) of self-expanding devices [ 37 ]. Endothelial injury and foreign material placement trigger the immune response, which begins with fibrinogen adsorption and platelet activation followed by recruitment of circulating leukocytes [ 37 ].…”
Section: Framementioning
confidence: 99%
See 1 more Smart Citation